Addressing conflict through collective action in natural resource management - Blake D Ratner; Ruth Meinzen-Dick; Jon Hellin; Everisto Mapedza; Jon Unruh; Wouter Veening; Eric Haglund; Candace May; Carl Bruch (International Journal of the Commons, 2017)
The food security crisis and international “land grabs” have drawn renewed attention to the role of natural resource competition in the livelihoods of the rural poor. While significant empirical research has focused on diagnosing the links between natural resource competition and (violent) conflict, much less has focused on the dynamics of whether and how resource competition can be transformed to strengthen social-ecological resilience and mitigate conflict. Focusing on this latter theme, this review synthesizes evidence from cases in Africa, Asia, and Latin America. Building on an analytical framework designed to enable such comparative analysis, we present several propositions about the dynamics of conflict and collective action in natural resource management, and a series of recommendations for action. These propositions are: that collective action in natural resource management is influenced by the social-ecological and governance context, that natural resource management institutions affect the incentives for conflict or cooperation, and that the outcomes of these interactions influence future conflict risk, livelihoods, and resource sustainability. Action recommendations concern policies addressing resource tenure, conflict resolution mechanisms, and social inequalities, as well as strategies to strengthen collective action institutions in the natural resource sectors and to enable more equitable engagement by marginalized groups in dialogue and negotiation over resource access and use.